Towards a spatial perspective: An integrative review of research on organisational space - Weinfurtner, Tania; Seidl, David (Scandinavian journal of management, 2019)
•Based on a review of the existing literature, we identify three concepts that underlie the notion of organisational space: boundaries, distance and movement.•We identify and discuss four spatial themes in the existing organisation literature: distribution in space, isolation of space, differentiation of spaces and intersection of spaces.•We develop an integrated research framework for studying organisational phenomena from a spatial perspective. Although the notion of space has gained considerable attention in organisation studies, it remains vague, and the respective literature is fragmented. In this paper, we review the empirical literature on organisational space with the aim of synthesising the findings of existing research and thereby facilitating the development of cumulative knowledge in this field. We highlight three dominant concepts that define space: boundaries, distance and movement. Furthermore, we identify four major spatial themes: the distribution of positions in space, the isolation of space, the differentiation of spaces and the intersection of distinct spaces. On that basis, we develop a comprehensive research framework and propose an agenda for future research on organisations from a spatial perspective.